Superhuman Marxism in Mark Millar’s Red Son - Arief Rahmat Nento (TRANSBAHASA, 2020)
The object of this research is a Graphic Novel entitled “Superman: Red Son” by Mark Millar. The novel is a story about a Superman in a different universe who lived amongst the society of communist and was raised by communist Ideology, involving issues of social nomenclature. The basis of this research resides in Marxism Theory and Graphic Novel. This research aims to determine the message conveyed behind the book as either critique or support towards the ideas of Communism. This research applied qualitative descriptive method and Marxist Literary Criticism as its Literary Approach. The Research Result pointed out that the book significantly showcased how far the success of Communism could go, especially with a Superhuman leader by their side. Simultaneously, the results also indicated that this work also represents critique upon Communism failures, specifically over the downfall of a utopian state the Super-powered leader had worked so hard for. This research revealed how Marxism could ideologically endure and survive, despite being overpowered by relentless Americans. It also shows that despite having a Superhuman leader, several problems became the factor of Communism failure in both the book and in reality remains unaverted.